Looking for Novelty in an “Old” Receptor: Recent Advances Toward Our Understanding of GABAARs and Their Implications in Receptor Pharmacology - Castellano, David; Shepard, Ryan David; Lu, Wei (Frontiers in Neuroscience, 2021)
Diverse populations of GABAA receptors (GABAARs) throughout the brain mediate fast inhibitory transmission and are modulated by various endogenous ligands and therapeutic drugs. Deficits in GABAAR signaling underlie the pathophysiology behind neurological and neuropsychiatric disorders such as epilepsy, anxiety, and depression. Pharmacological intervention for these disorders relies on several drug classes that target GABAARs for symptom management, such as benzodiazepines and more recently neurosteroids. It has been widely demonstrated that subunit composition and receptor stoichiometry impact the biophysical and pharmacological properties of GABAARs. However, current GABAAR-targeting drugs have limited subunit selectivity and produce their therapeutic effects concomitantly with undesired side effects. Therefore, there is still a need to develop more selective GABAAR pharmaceuticals, as well as evaluate the potential for developing next-generation drugs that can target accessory proteins associated with native GABAAR s. In this review, we briefly discuss the effects of benzodiazepines and neurosteroids on GABAARs, their use as therapeutics, and some of the pitfalls associated with their adverse side effects. We also discuss recent advances towards understanding the structure, function, and pharmacology of GABAARs with a focus on benzodiazepines and neurosteroids, as well as newly identified transmembrane proteins that modulate GABAARs.